Prevalence of Sexual Dysfunction Based on Female Sexual Function Index and Perception of Newly Bride in Jati Village and Its Related Factors - Angga J. Suryadi (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To found prevalence of female sexual dysfunction based on FSFI and perception of newly bride in Jati Village and its related factors. Method: A cross-sectional study was conducted in 33 newlybrides in Jati Village, East Jakarta, who got married for the first time within less than 6 months and did not have severe disease. We translated and validated the Female Sexual Function Index (FSFI) and added items on sexual dysfunction perception. The questionnaires were self-administered by the respondents. Results: Almost half (42.4%) of the participants were 26 - 30 years old. The most frequent sexual dysfunction domains were sexual arousal disorder and sexual pain. Frequency of sexual intercourse was significantly associated with sexual dysfunction based on FSFI. Marital age and frequency of sexual intercourse were significantly associated with sexual dysfunction based on participants’ perception. Agreement between FSFI score and sexual dysfunction perception was substantial (Kappa = 0.615, p < 0.001). Conclusion: The sexual dysfunction prevalence based on FSFI was 15.2% and based on perception was 12.1%. Participants age and frequency of sexual intercourse had a significant relationship with sexual dysfunction. Most of participants who felt that they had sexual dysfunction did not seek for medical services. [Indones J Obstet Gynecol 2010; 34-4: 170-4] Keywords: FSFI, newly bride, prevalence, sexual dysfunction